Assessment of surface settlement induced by tunnel excavations for the Esenler–Başakşehir (Istanbul, Turkey) Subway Line - Topal, Candaş; Mahmutoğlu, Yılmaz (Springer Science and Business Media LLC, 2021)
In most modern cities, public transportation demands are being addressed by constructing subways. The construction of tunnels, especially in weak and shallow subsurface strata, may cause significant damage to infrastructure and superstructures, however. In this study, surface deformations at four different locations along the Esenler–Basaksehir subway line, which is situated on the European side of Istanbul, were examined, with the aim of determining an appropriate method for the reliable estimation of settlement caused by shallow subsurface excavations in locations at high risk of damage. In this context, data from monitoring and numerical analysis were assessed together. Where horizontal, closely spaced twin tunnels were excavated consecutively at the same elevation, it was found that the excavation of the first tunnel disturbed the geological strata to the extent that the second tunnel encountered problems with those strata. Accordingly, it was observed that the maximum surface settlement caused by the first tunnel increased following excavation of the second tunnel, even though it had the same excavation geometry, and the settlement trough slid asymmetrically over the second tunnel.